Digital transformation management for agile organizations : a compass to sail the digital world - Bresciani, Stefano (Emerald Publishing Limited, 2021)
Digital Transformation Management for Agile Organizations highlights and explores new dynamics regarding current digital developments globally scale, by examining the threats, as well as the opportunities these innovations offer to organizations of all kinds. Digital transformation is addressed from an organizational standpoint and is examined in relation to differing management theories in the work. This ground-breaking study discusses how digital transformation can and is being embraced by a range of companies, as well as demonstrating how digital expansion is resulting in specific economic and social consequences. The authors present chapters providing wide-ranging coverage of digital transformation, with exploration of digital transformation as a process for business model innovation, digital marketing, leadership and establishing new business ecosystems. Digital Transformation Management for Agile Organizations is essential reading for all academic researchers with a focus on innovation management, technology management, human resource management, and strategy and leadership.